A Discourse Analysis on Deixis Used in “Night Changes” Song by One Direction - Jon Salvator Adhi Keo; Agustinus Simamora; Meliana Br. Siahaan; Carolin Panjaitand; Rahel Manik; Herman Herman (Journal of English Language and Education, 2023)
The purpose of this study is to conduct an analysis and determine which deixis are present in the song "Night Changes" by One Direction. The lyrics to the song are the focus of this particular piece of research "Night Changes" by One Direction. The researcher dissects and investigates each and every line in One Direction's song "Night Changes" in order to make it simpler to sample the words of the deixis contained inside the song. In the future, the results from the song's deixis information "Night Changes" will be evaluated in order to further define and categorize the different types of deixis; this study employs a qualitative methodology with realistic analysis results. The author of this study conducted an analysis of a song by One Direction titled "Night Changes" and discovered various types of deixis that frequently appear in each verse of the song's lyrics. These types of deixis include person deixis and temporal deixis, respectively. The specific individual deixis is utilized most frequently throughout the song "Night Changes" by One Direction, making it the song's primary focus deixis.